2000
DOI: 10.1177/019262330002800505
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Transforming Growth Factor Alpha in Chemically Induced Rat Hepatocellular Carcinomas with Reference to Differentiation and Proliferation

Abstract: Hepatocellular carcinomas (HCCs) were induced in male Fischer 344 rats with dietary 3'-methyl-4-(dimethylamino)-azobenzene treatment and were classified into solid, glandular (well-or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…These results are in line with the previous report describing increased TGF-alpha mRNA expression in proliferating hepatocytes [8] and neoplastic rat liver lesions [5,6,10].…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These results are in line with the previous report describing increased TGF-alpha mRNA expression in proliferating hepatocytes [8] and neoplastic rat liver lesions [5,6,10].…”
supporting
confidence: 93%
“…TGF-alpha tended to be positive and localized in the nucleus in highly proliferating areas zones 1 and 2, with peaks at 24-36 hr after PH. Kobayashi et al [6] demonstrated that expression of TGFalpha and its immunohistochemical localization was linked to cell proliferation in chemically induced rat hepatocellular carcinoma. Likewise, we recently reported TGF-alpha expression in the nucleus to be associated with malignancy and cell proliferation in chemically induced mouse hepatocellular tumors [10].…”
mentioning
confidence: 99%
“…Several studies have pointed to TGF-a overexpression playing an important role in hepatocarcinogenesis (12,25,29). Recently, we reported linkages to cell proliferation in chemically induced rat HCCs (16). From the literature, as well as the present study, TGF-a expression may be associated with cell proliferation activity of hepatocellular tumor cells.…”
Section: Discussionsupporting
confidence: 71%
“…Recently, we and others observed positive immunostaining of TGF-␣ in the nucleus of hepatocytes. [13][14][15][16] Nuclear location has been reported for many other polypeptide ligands (e.g., EGF, insulin, platelet-derived growth factor, nerve growth factor, parathyroid hormone-related protein, prolactin, interleukin 1, somatostatin, and fibroblast growth factor 1 and 2). Sometimes polypeptide ligands seem to colocalize with their respective receptors in the nucleus [17][18][19] ; the nuclear location of some of these growth factors coincided with DNA replication, as documented best for fibroblast growth factor 2.…”
mentioning
confidence: 99%